2017
DOI: 10.1017/jfm.2017.779
|View full text |Cite
|
Sign up to set email alerts
|

Optimal heat transfer enhancement in plane Couette flow

Abstract: Optimal heat transfer enhancement has been explored theoretically in plane Couette flow. The velocity field to be optimised is time-independent and incompressible, and temperature is determined in terms of the velocity as a solution to an advection-diffusion equation. The Prandtl number is set to unity, and consistent boundary conditions are imposed on the velocity and the temperature fields. The excess of a wall heat flux (or equivalently total scalar dissipation) over total energy dissipation is taken as an … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 42 publications
3
39
0
Order By: Relevance
“…We wonder exactly how large Pe must be for the higher modes to play a significant role in optimizing heat transport in a two-dimensional fluid layer. The three-dimensional computations reported in Motoki et al (2018a) show a stark difference in flow structures and transport scaling as compared to the two-dimensional flows for both stress-free boundaries from Hassanzadeh et al (2014) and no-slip boundaries from §4 of the present paper (see also Motoki et al (2018b)). Three-dimensional versions of branching appear to achieve the optimal scaling Nu ∼ Pe 2/3 already for Pe ∈ [10 3 , 10 4 ] with a prefactor within 10% of the background upper bound computations from Plasting & Kerswell (2003).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…We wonder exactly how large Pe must be for the higher modes to play a significant role in optimizing heat transport in a two-dimensional fluid layer. The three-dimensional computations reported in Motoki et al (2018a) show a stark difference in flow structures and transport scaling as compared to the two-dimensional flows for both stress-free boundaries from Hassanzadeh et al (2014) and no-slip boundaries from §4 of the present paper (see also Motoki et al (2018b)). Three-dimensional versions of branching appear to achieve the optimal scaling Nu ∼ Pe 2/3 already for Pe ∈ [10 3 , 10 4 ] with a prefactor within 10% of the background upper bound computations from Plasting & Kerswell (2003).…”
Section: Discussionmentioning
confidence: 56%
“…This strictly enforces the advection-diffusion equation and its adjoint at every time-step, Utilising δF δu to compute corrections to the flow field. This approach was taken in Motoki et al (2018b), and the rate limiting step is the solution of the advectiondiffusion equation and its adjoint. In the present work, we take a different approach and compute numerical solutions to (3.3) and (3.8) Utilising two different algorithms.…”
Section: Gradient Ascent Methodsmentioning
confidence: 99%
“…Near the walls, meanwhile, selfsimilar vortical structures locally enhance heat transfer, and yield logarithmic mean temperature distribution. Our earlier optimisation for heat transfer in plane Couette flow (Motoki et al 2018) provided the optimal velocity fields in which we observed hierarchical structure consisting of a number of streamwise vortex tubes. The logarithmic mean temperature profiles as well as the ultimate scaling N u ∼ Ra 1/2 were also found in the optimal fields.…”
Section: Discussionmentioning
confidence: 97%
“…This is because G = F − (µ/2)P e 2 and thus the Euler-Lagrange equations for G are also given by (2.8)-(2.11). In our previous work on a different functional in a different configuration (Motoki et al 2018), we have developed a numerical approach to find local maxima of a functional kindred to G by a combination of the steepest ascent method and the Newton-Krylov method. Using the same procedures, we obtain an optimal state (u opt , θ opt , θ * opt , p * opt ) maximising G for given µ.…”
Section: Numerical Optimisationmentioning
confidence: 99%
See 1 more Smart Citation